2009
DOI: 10.12657/folmal.008.024
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of European Lymnaeidae (Gastropoda: Pulmonata) in studies with the use of molecular biology techniques. I. Preliminary view on the subgenus Stagnicola Leach, 1830 on the basis of RAPD analysis

Abstract: The random amplified polymorphic DNA (RAPD) technique was used to study genomic relationships of five lymnaeid species:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…p. turricula (baRGues et al 2001, 2003). Our earlier studies (Rybska et al 2000a(Rybska et al , b, 2008(Rybska et al , wesołowska 2010 were not decisive and confirmed a close relationship between these two taxa. However, with our new molecular and chorological data (preliminarily presented in Pieńkowska et al 2008a, b and banasiak 2011 as well as in Rybska & lesicki 2005, respectively) we decided to verify the opposite view -that the two taxa are two distinct but closely related species, i.e.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…p. turricula (baRGues et al 2001, 2003). Our earlier studies (Rybska et al 2000a(Rybska et al , b, 2008(Rybska et al , wesołowska 2010 were not decisive and confirmed a close relationship between these two taxa. However, with our new molecular and chorological data (preliminarily presented in Pieńkowska et al 2008a, b and banasiak 2011 as well as in Rybska & lesicki 2005, respectively) we decided to verify the opposite view -that the two taxa are two distinct but closely related species, i.e.…”
Section: Introductionsupporting
confidence: 61%
“…Unexpectedly, we also found six new localities of S. palustris in south-eastern Poland (Fig. 4, (Jackiewicz 1993, FalkneR 1995, FalkneR et al 2001, GlöeR 2002, GlöeR & meieR-bRook 2003 as well as on the molecular features found in the nucleotide sequences of ITS1 and ITS2 fragments in rDNA gene (baRGues et al 2001(baRGues et al , 2006 and obtained with the use of RAPD technique (Rybska et al 2000a(Rybska et al , b, 2008. The distinct species status of these three taxa is confirmed by the results of this study.…”
Section: Distribution Of Stagnicola Palustris and S Turricula In Polandmentioning
confidence: 54%
See 2 more Smart Citations
“…: Stagnicola palustris palustris and Stagnicola palustris turricula. However, their previous molecular survey (Rybska et al, 2000) confirmed the separate status of S. turricula as a species. Undoubtedly, the separate status of S. turricula as a species has also been confirmed by other European malacologists (Jackiewicz, 2000a;Falkner et al, 2001;Glöer, 2002;Fauna Europaea, 2004;Piechocki, 2008).…”
Section: Discussionmentioning
confidence: 94%